2017
DOI: 10.1177/1933719116667222
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ezrin and Estrogen Receptors During Cervical Carcinogenesis

Abstract: During cervical carcinogenesis, the usual relationship between estrogen and ezrin induction is abridged. This is consistent with the effects of human papilloma virus viral proteins such as E6 and E7 that upregulate SIX1, a protein that induces ezrin. Cervical carcinogenesis is progressive but arrests at the preinvasive stage for varying lengths of time. These studies suggest that changes in ezrin may be associated with the development of the invasive phenotype and penetration of the basement membrane. They als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…More than 80% of cervical cancer samples exhibit high Ezrin expression and a decrease in E-cadherin levels, which can be detected using immunohistochemistry and cervical smears (Zacapala-Gomez et al, 2018). Consistent with this study, the overlapping of Ezrin and estrogen receptor expression during cervical carcinogenesis raises the possibility that Ezrin is associated with the penetration of the basement membrane (Fadiel et al, 2017). Therefore, Ezrin controls adhesion and the invasiveness of cancer cells through the interactions between cell adhesion molecules, suggesting a role in developing cervical neoplasia and cancer.…”
Section: Ezrin In Cervical Cancersupporting
confidence: 86%
See 1 more Smart Citation
“…More than 80% of cervical cancer samples exhibit high Ezrin expression and a decrease in E-cadherin levels, which can be detected using immunohistochemistry and cervical smears (Zacapala-Gomez et al, 2018). Consistent with this study, the overlapping of Ezrin and estrogen receptor expression during cervical carcinogenesis raises the possibility that Ezrin is associated with the penetration of the basement membrane (Fadiel et al, 2017). Therefore, Ezrin controls adhesion and the invasiveness of cancer cells through the interactions between cell adhesion molecules, suggesting a role in developing cervical neoplasia and cancer.…”
Section: Ezrin In Cervical Cancersupporting
confidence: 86%
“…LGALS1, Galectin-3, E-cadherin, MAPK JNK/p38 and Akt/ERK1/2 signaling Controls cell adhesion and enhances invasion. Serves as the cervical cancer marker for non-invasive detection Elliott et al, 2005;Saito et al, 2013;Kong et al, 2016;Fadiel et al, 2017;Li et al, 2017;Zacapala-Gomez et al, 2018;Chetry et al, 2020 Gastric cancer miR-183 Antagonizes mi-183 actions, and is correlated with tumor size, invasion lymph node and metastasis Li et al, 2011;Cao et al, 2014 Osteosarcoma miR-183, Akt and MAPK, Akt/mTOR Promotes tumor metastasis. High expression is correlated with poor prognosis Khanna et al, 2004;Krishnan et al, 2006 Hepatocellular cancer…”
Section: Ezrin In Lung Cancermentioning
confidence: 99%
“…It has been demonstrated that Ezrin expression is higher in invasive or metastatic tumors [ 18 , 26 ], and Ezrin expression is necessary for the invasive ability of cervical tumor cells through induction of epithelial-mesenchymal transition (EMT) [ 20 ]. These data are related with the overexpression of Six1, which is a transcription factor for Ezrin, reported in cervical cancer tissue [ 26 ], and has been reported that Six1 overexpression promoted EMT at early stages of HPV16-mediated transformation of human keratinocytes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that Ezrin is overexpressed in cervical cancer or intraepithelial neoplasia (CIN) compared to normal cervical tissue [ 16 19 ]. Interestingly, Ezrin expression was higher in invasive cancer and metastatic cancer [ 18 ]. Ezrin expression is involved in cell migration and invasion in cervical cancer cell lines HeLa and SiHa, it has been suggested that Ezrin could promote cervical cancer progression through regulation of epithelial-mesenchymal transition [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of DNA repair gene O-6-methylguanine-DNA methyltransferase (MGMT) promoter region has been correlated with better prognosis of glioblastoma multiforme [14]. Ezrin can promote cellular movement and motility as well as controlling cellular growth, whereby contributing to tumorigenesis, invasion, and metastasis [15]. Ezrin was previously found to be overexpressed in CC and its expression was actively involved in metastasis and poor prognosis [16].…”
Section: Introductionmentioning
confidence: 99%